(untitled) (Journal of Applied Learning and Teaching, 2020)
The number of international students is increasing rapidly and impacting teaching and learning at colleges and universities (Anayah & Kuk, 2015). While many international students successfully complete their degrees, others face challenges due to a lack of academic, cultural and linguistic understanding. This study reports the results of a survey that examines the perspectives of 89 North American university professors regarding international students’ linguistic and academic needs for university. The survey findings revealed that international students’ limited English proficiency hinders them from succeeding at university. The results also show that international students need to develop a better understanding of American classroom culture.